2024
DOI: 10.1101/2024.02.25.581947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Holimap: an accurate and efficient method for solving stochastic gene network dynamics

Chen Jia,
Ramon Grima

Abstract: Gene-gene interactions are crucial to the control of sub-cellular processes but our understanding of their stochastic dynamics is hindered by the lack of simulation methods that can accurately and efficiently predict how the distributions of protein numbers for each gene vary across parameter space. To overcome these difficulties, here we present Holimap (high-order linear-mapping approximation), an approach that approximates the protein number distributions of a complex gene network by the distributions of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…For simplicity and analytical tractability, we here only derive the switching time distributions in an autoregulatory feedback loop. We anticipate that the results in the present paper can be generalized to more complex gene regulatory networks [26, 41]. In addition, while we have an implicit effective description of mRNA and protein dilution due to cell division, via the effective mRNA and protein decay rates, it has recently been shown that, in some parameter regimes, this type of model cannot capture the stochastic dynamics predicted by models with an explicit description of the cell cycle [42, 43].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For simplicity and analytical tractability, we here only derive the switching time distributions in an autoregulatory feedback loop. We anticipate that the results in the present paper can be generalized to more complex gene regulatory networks [26, 41]. In addition, while we have an implicit effective description of mRNA and protein dilution due to cell division, via the effective mRNA and protein decay rates, it has recently been shown that, in some parameter regimes, this type of model cannot capture the stochastic dynamics predicted by models with an explicit description of the cell cycle [42, 43].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Despite the potential risks, we found that fitting these complex models to the telegraph model still provide a large amount of valuable information. In fact, the idea of using the distribution of the telegraph model to approximate that of a complex model has been applied in previous studies using analytical PLOS COMPUTATIONAL BIOLOGY methods such as linear mapping or moment matching [89][90][91]. Here we evaluate the performance of the effective telegraph model using statistical and computational methods.…”
Section: Conclusion and Discussionmentioning
confidence: 99%